Enantioselective transfer hydrogenation of pro-chiral ketones catalyzed by novel ruthenium and iridium complexes of well-designed phosphinite ligand - Arslan, Nevin (PHOSPHORUS SULFUR AND SILICON AND THE RELATED ELEMENTS, 2019)
The interaction of [Ru(eta(6)-arene)(mu-Cl)Cl](2) and Ir(eta(5)-C5Me5)(mu-Cl)Cl](2) with a new Ionic Liquid-based phosphinite ligand, [(Ph2PO)-C6H9N2Ph]Cl, (2) gave [Ru((Ph2PO)-C6H9N2Ph)(eta(6)-p-cymene)Cl-2]Cl (3), [Ru((Ph2PO)-C6H9N2Ph)(benzene)Cl-2]Cl (4) and [Ir((Ph2PO)-C6H9N2Ph)(C5Me5)Cl-2]Cl (5), complexes. All the compounds were characterized by a combination of multinuclear NMR and IR spectroscopy as well as elemental analysis. Furthermore, the Ru(II) and Ir(III) catalysts were applied to asymmetric transfer hydrogenation of acetophenone derivatives using 2-propanol as a hydrogen source. The results showed that the corresponding alcohols could be obtained with good activity (up to 55% ee and 99% conversion) under mild conditions. Notably, [Ir((Ph2PO)-C6H9N2Ph)(C5Me5)Cl-2]Cl (5) is more active than the other analogous complexes in the transfer hydrogenation (up to 81% ee).
Keywords: Enantioselective transfer hydrogenation; Homogeneous catalysis; Chiral phosphinite ligand; Ruthenium(II); Iridium(III)